Design of a Smart Solar Hybrid Egg Incubator for Small Scale Poultry Farmers - Abba-Aji, M. A.; Usman, A. R.; Shuwa, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
In this study, an electro-mechanical device (incubator) was designed to provide temperature and humidity for fertilization of eggs. A 132 capacity egg crates and medium density fiber board plywood (MDF-plywood) with a 15mm thickness for the incubation chamber were used. A 200AH lithium phosphate battery, 300W capacity solar panel and inverter were used to power the 200W electric bulb and other incubator components in the time of power shortages. Incubation temperature of 37.50C and average relative humidity of 45% were considered during the design. A 3D model of the designed incubator was produced using Solid works software package. The model provided some important information on the material properties of the proposed plywood for construction of the casing, the plastic egg crates and the egg turning tray. The required number of egg crates and egg turning trays were determined as 8 and 4 respectively with two plastic crates sitting on each tray. Heat generation and heat losses of the system were also determined as 139.482595W and-3.395925W respectively. The total power consumption of the designed incubator was 150.4159W. Design of a cost-effective solar hybrid eggs incubator (N940, 200), with a dimension of 1100mm for poultry farmers was successfully carried out with a hatching capacity of 1056eggs.